2021
DOI: 10.1002/ange.202105529
|View full text |Cite
|
Sign up to set email alerts
|

Das 1,3‐Bis(tricyanoboran)imidazolin‐2‐ylidenat‐Anion – Ein ditopischer dianionischer N‐heterocyclischer Carben‐Ligand

Abstract: Das 1,3‐Bis(tricyanoboran)imidazolat‐Anion 1 wurde in hoher Ausbeute ausgehend von Lithiumimidazolat und B(CN)3‐Pyridin‐Addukt erhalten. Das Anion 1 ist chemisch sehr robust, was sich in der Isolierung des H5O2+‐Salzes widerspiegelt. Ferner dient 1 als Startmaterial für das neuartige dianionische N‐heterocyclische Carben (NHC), das 1,3‐Bis(tricyanoboran)imidazolin‐2‐ylidenat‐Anion 3, das mit seinem Carben‐Kohlenstoffatom und den Cyano‐Gruppen an Bor ein ditopischer Ligand ist. Erste Reaktionen des neuen NHC 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 91 publications
(75 reference statements)
1
7
0
Order By: Relevance
“…The small 1 J( 77 Se, 13 C) coupling constant of Li8 • (THF) 1.5 of 206.0 Hz underlines the strong σ-donor ability of 6 compared to Ani-cAAC-B(CN) 3 , which is 5) pm [20] and IB(CN) 3 2À (III) d(C=Se) = 184.2(4) pm. [14] The Li ion in Li8 • (THF) 2 is tetrahedrally coordinated by the O atoms of two THF ligands, the boron bonded fluorine substituent F1, and Se1.…”
Section: àmentioning
confidence: 99%
See 3 more Smart Citations
“…The small 1 J( 77 Se, 13 C) coupling constant of Li8 • (THF) 1.5 of 206.0 Hz underlines the strong σ-donor ability of 6 compared to Ani-cAAC-B(CN) 3 , which is 5) pm [20] and IB(CN) 3 2À (III) d(C=Se) = 184.2(4) pm. [14] The Li ion in Li8 • (THF) 2 is tetrahedrally coordinated by the O atoms of two THF ligands, the boron bonded fluorine substituent F1, and Se1.…”
Section: àmentioning
confidence: 99%
“…So, it is larger than %V bur reported for cAAC Me -5 (38.0 %) [34] and identical to %V bur reported for IB(CN) 3 2À (III). [14] Noteworthy, a significantly larger %V bur of 43.3 % was evaluated for 6 from the structural parameters of the selenium compound Li8 • (THF) 2 (see steric maps in the SI). This difference in %V bur is attributed to the rotational freedom of the C 2 F 5 BF 2 unit, rendering Ani-cAAC 6 a ligand with a flexible steric environment.…”
Section: àmentioning
confidence: 99%
See 2 more Smart Citations
“…Tamm, Nomura and coworkers demonstrated that anionic NHC ligands 16 featuring a B(C 6 F 5 ) 3 moiety in the NHC backbone can substitute a chloride ligand of [V(NR)Cl 3 ] to yield vanadium( v ) imido complexes [V(NR)Cl 2 (WCA-NHC)] (WCA = B(C 6 F 5 ) 3 , R = adamantyl, phenyl, 2,6-dimethylphenyl). These complexes are active catalysts for the ethylene polymerization in presence of Al i Bu 3 .…”
Section: Introductionmentioning
confidence: 99%